SUMO conjugation to promoter-proximal sequence elements–associated proteins impacts on snRNA transcription - Laureano Bragado; Berta Pozzi; Inés Beckerman; Melina Magalnik; Anabella Srebrow (Proceedings of the National Academy of Sciences, 2025)
The noncoding small nuclear RNAs (snRNAs) associate with a large set of proteins to form small nuclear ribonucleoprotein particles (snRNPs). While the function of snRNAs is well characterized, the regulation of their transcription remains poorly understood. Recently, we demonstrated that SUMO conjugation regulates snRNA3′ end processing. To further study the connection between SUMOylation and snRNA biogenesis, we generated a CRISPR/dCas9 tool comprising a catalytically inactive Cas9 (dCas9) fused to the catalytic domain of the SUMO protease SENP1 (dCas9-SENP1). Here, we show that snRNA transcription decreases when dCas9-SENP1 is delivered to their promoter-proximal sequence elements (PSE), indicating that SUMO conjugation to proteins associated with snRNA promoters is necessary for proper transcriptional activity. Focusing on SNAPC1, a subunit of the snRNA-specific transcription complex SNAPc, we identified lysine residues 245 and 333 as SUMO acceptor sites and generated a SUMOylation-deficient mutant of this protein (SNAPC1 2KR). To explore the relevance of SNAPC1 SUMOylation on snRNA transcription, we generated a cell line carrying an inducible degron system for depletion of the endogenous SNAPC1 protein. This system led us to demonstrate that SNAPC1 2KR is unable to sustain basal levels of snRNA transcription. By tagging endogenous SNAPC3 and SNAPC4, two other subunits of SNAPc, we show that while SNAPC1 SUMOylation-deficient mutant is able to interact with SNAPC3, its interaction with SNAPC4 is affected, despite the fact it is still recruited to the PSE. Altogether, these results indicate that SNAPC1 SUMOylation is required for proper snRNA transcription and SNAPc complex assembly.